Islamic moderation in education and the phenomenon of cyberterrorism: a systematic literature review - Syamsul Ma'arif; Hamidulloh Ibda; Farid Ahmadi; Nanang Qosim; Nur Alfi Muanayah (Institute of Advanced Engineering and Science, 2023)
This article presents a systematic literature review on Islamic moderation in education to prevent cyberterrorism in the latest literature. The method used is the systematic literature review and preferred reporting items for systematic reviews and meta-analyses protocol with the stages of identification, screening, eligibility, inclusion, abstraction, and data analysis assisted by PoP 7, VOSviewer, and NVIVO 12 plus. The search results in Scopus contained 1,252 articles, then filtered according to compatible themes into 54. The topic findings are the concept of Islamic moderation, Islamic moderation in preventing cyberterrorism in education, cyberterrorism, cyberterrorism phenomenon, terrorism, religious moderation, wasatiyyah, peaceful coexistence, and counter-terrorism. The findings of the results mention that Islamic moderation is a way of religion according to the principles of the Quran and Sunnah, namely ummah wasatan, which is applied to education. Cyberterrorism phenomenon curs in various parts of the world, including in education, which is spread through cyberspace to intimidate, spread fear, and destroy the order of life in terrorist groups. Islamic moderation plays a role in preventing cyberterrorism in education through ideological approaches to radical organisations, accommodation of local culture, digital literacy, counter-narrative and deradicalisation, digital media mastery, digital media peaceful, and soft power deterrence. Future research needs to explore Islamic moderation according to the times.